Emergency care: knowledge and applicability of the Manchester protocol by nurses (Research, Society and Development, 2021)
This is an integrative literature review on emergency screening and applicability of the Manchester protocol by nurses, professional who has been responsible for this demand. The main objective of the study was to show what knowledge is needed for the application of the Manchester protocol by nurses. The search took place in the “LILACS”, “BDENF” and “MEDLINE” databases via the BVS. It was concluded that there is a need for more studies on the subject, in addition to listing the knowledge necessary for the application of this protocol by the nurse.